Zakat Atas Hak Kekayaan Intelektual Perspektif Teori An-Nama’ Yusuf Qaradhawi - Imam Agung Prakoso (Volksgeist: Jurnal Ilmu Hukum dan Konstitusi, 2020)
This article aims to find out the Intellectual Property Rights according to an-Nama’ Yusuf Qardhawi theory Qardhawi' and how the zakat is calculated. The underlying theories used in this study are zakat theory an-Nama’, zakat profession, intellectual property right as a form of wealth, and intangible property. This study is a content analysis using normative legal approach. The research method used in this study is library research by collecting the data from primary and secondary data. The data is analyzed using interactive model. The findings showed that zakat on Intellectual Property Rights based on an-Nama’ theory by Yusuf Qaradhawi is a part of zakat on profession because IPRs have economic value, obtained from intellectual creativity manifested in the forms of works. Therefore, IPRs are a form of intangible property that could develop. In addition, the calculation of zakat on IPR is 2.5% of the income earned after deducted by tax obligations.